Specioside (SS) & verminoside (VS) (Iridoid glycosides): isolation, characterization and comparable quantum chemical studies using density functional theory (DFT). Issue 1 (January 2019) - Saini, Monika; Sangwan, Reetu; Khan, Mohammad Faheem; Kumar, Ashok; Verma, Ruchi; Jain, Sudha
Abstract: Two biologically important molecules specioside (SS) and verminoside (VS) have been isolated from the ethanolic extract of stem bark of Kigelia pinnata . We have explored the electronic and spectroscopic properties of these two molecules on the basis of the Density Function Theory (DFT) quantum chemical calculations along with the correlations of biological efficacies and the results are presented in this paper. The structures of the molecules were established with the help of spectroscopic techniques ( 1 H, 13 C NMR, UV-VIS, FTIR) and chemical reactivity was compared by computed DFT theory using Becke3-Lee-Yang-Parr (B3LYP)/6-31G (d, p) data basis set. UV-Visible spectrum was obtained using Time Dependent DFT method. Electric dipole moment, polarizability, first static hyper polarizability and hyper conjugative interactions were also studied with the aid of natural bond orbital (NBO) analysis of these two compounds. The thermodynamic parameters of these compounds were determined at various temperatures. The HOMO, LUMO, chemical hardness (η), chemical potential (μ), electronegativity (χ), electrophilicity power (ω), the gap energy and NBO analysis of both the compounds have been discussed in this paper. Local reactivity was evaluated through the Fukui function i.